Lightweight high-strength power cable based on composite material and application thereof
By adopting composite material design in the cable, including composite aerogel and modified carbon balls, the problem of degradation of shielding capacity of existing cables in high electromagnetic interference environments is solved, and the lightweight and significant improvement of the cable's anti-electromagnetic interference performance is achieved.
Patent Information
- Application Number
- CN202510160582.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-13
- Publication Date
- 2025-03-11
- Estimated Expiration
- 2045-02-13
AI Technical Summary
The existing lightweight flexible reel cable has reduced shielding capabilities in high electromagnetic interference environments, and the lightweight improvement of a single component cannot meet the needs of modern power transmission for comprehensive excellent performance.
The composite material-based design is adopted, including a conductor layer, a lightweight shielding layer, a winding cladding layer and a composite sheath layer. By using materials such as composite aerogel and modified carbon balls, the lightweight and electromagnetic interference resistance of the cable are improved through the coordinated cooperation of the porous structure and hollow carbon balls.
It significantly improves the lightweight performance and anti-electromagnetic interference capability of the cable, enhances the thermal stability and flame retardant properties of the material, and meets the needs of modern power transmission for high strength, low density and excellent shielding performance.
Smart Images

Figure CN119601295A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of special cable preparation, and in particular to a lightweight and high-strength power cable based on composite materials and applications thereof. Background Art
[0002] Lightweight and electromagnetic shielding technologies are two core paths for the development of power cables, targeting the needs of weight optimization and anti-interference performance respectively. These two technologies have achieved significant progress through material innovation and technological breakthroughs.
[0003] In terms of lightweighting, cables have gradually evolved from traditional copper cables to aluminum alloy and carbon fiber composite materials, which significantly reduce weight while maintaining strength; in the field of electromagnetic shielding, shielding technology has gradually evolved from early copper mesh and aluminum foil to nanomaterials and flexible composite materials, further improving shielding effects and material adaptability. The maturity of these technologies provides lighter, more durable and anti-interference power transmission solutions for aerospace, electric vehicles, smart grids and other fields.
[0004] Prior art CN118919148B discloses a lightweight flexible reel cable, comprising an outer sheath, a reinforcement layer, an inner sheath, a mica tape layer, a ground wire and a main line, wherein the apparent density of the inner sheath is ≤0.35g / cm 3 , tensile strength ≥3.5MPa, the provided reel cable with inner sheath is light and high-strength, which can avoid adverse effects on the normal operation of the equipment and the performance of the cable itself due to excessive weight.
[0005] However, the above patent content is to prepare a lightweight flexible cable by foaming the inner sheath layer. However, after the inner sheath layer is foamed, a large number of tiny pores are introduced, which weaken the conductivity and shielding integrity of the sheath layer, resulting in a significant reduction in the electromagnetic interference shielding capability. In a high electromagnetic interference environment, this performance degradation may have an adverse effect on the stability and safety of equipment operation. Secondly, the lightweight improvement of a single component also has limitations in improving the overall performance. Due to the overall complexity of the cable structure, simply optimizing the weight of a certain component cannot meet the comprehensive requirements of modern power transmission for lightweight and excellent electromagnetic shielding performance.
[0006] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0007] The object of the present invention is to provide a lightweight and high-strength power cable based on a composite material and its application, so as to solve the technical problem in the prior art that the lightweight and anti-electromagnetic interference performance of lightweight cables need to be further improved.
[0008] The object of the present invention can be achieved by the following technical solution: A lightweight and high-strength power cable based on a composite material comprises a conductor layer, a lightweight shielding layer, a wrapping layer and a composite sheath layer arranged in sequence from the inside to the outside;
[0009] The conductor layer is composed of a plurality of copper wires twisted together and coated with polyvinylidene fluoride; the wrapping layer is obtained by wrapping a polyvinylidene fluoride wrapping tape around the outside of the composite aerogel; the composite sheath layer is composed of a composite cable material;
[0010] The lightweight shielding layer is obtained by coating the conductor layer with composite aerogel and fixing it with a wrapping tape; the composite sheath layer is obtained by melt-extruding a composite cable material onto the surface of the wrapping layer and shaping it, wherein the composite cable material is a mixture of lightweight polyurethane, flame retardant, plasticizer, ultraviolet absorber and lubricant in a mass ratio of 70-85g:10-15g:5-8g:0.2-0.5g:3-5g.
[0011] Furthermore, the flame retardant is one or two of melamine and hexabromocyclododecane; the plasticizer is one or more of dioctyl phthalate, diisooctyl phthalate and epoxy soybean oil; the ultraviolet absorber is one or two of 2-hydroxy-4-octyloxybenzophenone and bis(2,2,6,6-tetramethylpiperidinyl)sebacate; the lubricant is one or more of calcium stearate, oxidized polyethylene wax and montan wax.
[0012] Furthermore, the preparation method of the composite aerogel comprises the following steps:
[0013] A1. Add modified carbon spheres, tetrabutyl titanate and deionized water into a reactor, stir at room temperature for 10-15 minutes, then dropwise add copper source solution into the reactor, and continue stirring for 5-8 minutes to obtain a composite solution;
[0014] A2, transferring the composite liquid to a hydrothermal reactor, raising the temperature of the hydrothermal reactor to 160-200°C, keeping the temperature for 20-28h, and post-treating to obtain a gel precursor;
[0015] A3. Transfer the gel precursor to a tubular furnace and calcine and reduce it to obtain a composite aerogel.
[0016] Reaction principle for preparing composite aerogel: Under hydrothermal conditions, tetrabutyl titanate and the siloxane structure on the surface of modified carbon spheres are hydrolyzed to produce a gel structure. The copper nitrate molecules inside the copper source liquid are attached to the surface of the gel structure, and then freeze-dried to obtain a gel precursor. After high-temperature hydrogen reduction, the copper salt on the surface of the gel precursor is reduced to copper particles, and finally a composite aerogel is prepared.
[0017] Further, in step A1, the stirring rate of the reactor is 60-80rpm, the amount ratio of modified carbon spheres, tetrabutyl titanate, deionized water and copper source solution is 4-6g:7-8g:60-80mL:10-20mL, and the copper source solution is obtained by mixing copper nitrate and ethylene glycol at a ratio of 1-2g:8-10mL;
[0018] Further, in step A2, the post-treatment includes: after the reaction is completed, after the temperature of the hydrothermal reactor is lowered to room temperature, the material is transferred to a stainless steel mold, and the stainless steel mold is transferred to a copper column immersed in liquid nitrogen, and after standing for 20-30 minutes, the mold is transferred to a vacuum dryer, the temperature is set to 30-50°C, the vacuum degree is 3-5mBar, and vacuum drying is performed for 1-2 hours to obtain a gel precursor;
[0019] Furthermore, in step A3, the calcination reduction operation is as follows: after nitrogen protection is introduced into the tubular furnace, the temperature is increased to 400-500°C at a heating rate of 3-5°C / min, the nitrogen is disconnected, and a mixed gas of hydrogen and nitrogen with a volume ratio of 4-5mL:95mL is introduced into the tubular furnace, and the mixture is kept warm for 30-40min, and naturally cooled to room temperature to obtain a composite aerogel.
[0020] Furthermore, the preparation method of the modified carbon spheres comprises the following steps:
[0021] B1. Disperse nano-calcium carbonate powder in a hydrothermal reactor filled with a carbon source solution, stir for 5-8 minutes at room temperature, raise the temperature of the hydrothermal reactor to 140-160°C, keep the reaction for 6-8 hours, and post-treat to obtain carbon-coated nanospheres;
[0022] B2, adding carbon-coated nanospheres and 49.0wt% sulfuric acid into a reactor, stirring at room temperature for 10-15min, adding potassium permanganate into the reactor, raising the temperature of the reactor to 40-50°C, keeping the temperature for 1-2h, and post-treating to obtain carbon shell hollow spheres;
[0023] B3. Add hollow carbon spheres and N,N-dimethylformamide into a reactor, introduce nitrogen protection, stir at room temperature for 5-8 minutes, add 3-isocyanatepropyltrimethoxysilane solution into the reactor, increase the temperature of the reactor to 30-50°C, keep warm for 30-40 minutes, and post-treat to obtain modified carbon spheres.
[0024] The reaction principle for preparing modified carbon spheres is as follows: under hydrothermal reaction, glucose in the carbon source solution is dehydrated and attached to the surface of nano-calcium carbonate powder to form an organic layer. After high-temperature carbonization, the nano-calcium carbonate powder is removed by acidic oxidizing liquid, the carbon layer is oxidized, and the siloxane structure is modified on its surface to obtain modified carbon spheres.
[0025] Further, in step B1, the stirring rate of the reactor is 60-80rpm, the amount ratio of the nano calcium carbonate powder and the carbon source solution is 1-2g:20-24mL, the carbon source solution is a glucose solution with a concentration of 0.5-0.8M, and the post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is transferred to a drying oven at a temperature of 60-80°C for vacuum drying, after the filter cake is constant in weight, the filter cake is transferred to a tubular furnace, after nitrogen protection is introduced, the tubular furnace is heated to 720°C at a heating rate of 5°C / min, and after calcination for 5h, it is naturally cooled to obtain carbon-coated nanospheres;
[0026] Further, in step B2, the stirring rate of the reactor is 60-80rpm, the amount ratio of carbon-coated nanospheres, 49.0wt% sulfuric acid and potassium permanganate is 2-3g:30-36mL:6-8g, and the post-treatment includes: after the reaction is completed, after the temperature of the reactor is lowered to room temperature, adding a protective sodium hydroxide solution to the reactor, adjusting the reaction solution to be neutral, filtering the reaction solution to collect the filter cake, washing the filter cake with anhydrous ethanol and deionized water for 3-5 times, and transferring the filter cake to a drying oven at a temperature of 60-80°C for vacuum drying until the filter cake has a constant weight, to obtain a carbon shell hollow sphere;
[0027] Furthermore, in step B3, the stirring rate of the reactor is 60-80rpm, the amount ratio of hollow carbon spheres, N,N-dimethylformamide and 3-isocyanatepropyltrimethoxysilane solution is 4-5g:30-40mL:10-12mL, and the 3-isocyanatepropyltrimethoxysilane solution is obtained by mixing 3-isocyanatepropyltrimethoxysilane and N,N-dimethylformamide in an amount ratio of 2-3g:10-15mL. The post-treatment includes: after the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is filtered with anhydrous ethanol 3-5 times, and the filter cake is transferred to a drying oven at a temperature of 60-80°C and vacuum dried until the filter cake has a constant weight to obtain modified carbon spheres.
[0028] Furthermore, the preparation method of the lightweight polyurethane comprises the following steps:
[0029] C1. Add hydroxy silicone oil, hydroquinone dihydroxyethyl ether, N,N-dimethylformamide and dibutyltin dilaurate into a reactor, introduce nitrogen protection, add meta-xylyl diisocyanate solution into the reactor, increase the temperature of the reactor to 50-60°C, keep the reaction temperature for 1-2h, and post-treat to obtain modified polyurethane;
[0030] C2. Add modified polyurethane and N,N-dimethylformamide into a reactor and stir. After the temperature of the reactor rises to 40-60°C, add 3-isocyanatepropyltrimethoxysilane solution into the reactor. After stirring for 30-40 minutes, add deionized water and sodium hydroxide powder into the reactor. After stirring for 5-8 minutes, add modified carbon balls into the reactor. Keep warm for 20-30 minutes, and obtain lightweight polyurethane by post-treatment.
[0031] The reaction equation for preparing lightweight polyurethane is:
[0032]
[0033] Where:
[0034] ;
[0035] ;
[0036] ;
[0037] “ ” indicates modified carbon spheres; “*” indicates active connection sites of organic chain segments.
[0038] The reaction principle for preparing lightweight polyurethane is as follows: during the reaction process, isocyanate is used as a cross-linking agent. Under the condition of a catalyst, the isocyanate group on isocyanate as an active group condenses with the hydroxyl groups on dihydroxyethyl hydroquinone and hydroxy silicone oil to form a segment co-embedded with dihydroxyethyl hydroquinone segment and a polysiloxane segment, and the isocyanate group end is converted into an amino-terminated modified polyurethane through hydrolysis. The isocyanate group on 3-isocyanatepropyltrimethoxysilane can react with the amino group on the modified polyurethane end to form a siloxane segment, and the lightweight polyurethane is obtained by co-hydrolysis with modified carbon spheres.
[0039] Further, in step C1, the amount ratio of hydroxy silicone oil, hydroquinone dihydroxyethyl ether, N,N-dimethylformamide, dibutyltin dilaurate and meta-phenylenedimethyl isocyanate solution is 8-10g:1-2g:40-60mL:0.2-0.5g:10-12mL, and the meta-phenylenedimethyl isocyanate solution is obtained by mixing meta-phenylenedimethyl isocyanate and N,N-dimethylformamide at an amount ratio of 3-4g:10-15mL. The post-treatment includes: after the reaction is completed, adding purified water to the reactor, raising the temperature of the reactor to 120-140°C, and distilling under reduced pressure until no liquid is produced to obtain a modified polyurethane;
[0040] Furthermore, the stirring rate of the reactor is 60-80rpm. In step C2, the amount ratio of modified polyurethane, N,N-dimethylformamide, 3-isocyanate propyl trimethoxy silane solution and modified carbon sphere is 8-10g:40-50mL:10-15mL:2-3g, and the 3-isocyanate propyl trimethoxy silane solution is obtained by mixing 3-isocyanate propyl trimethoxy silane and N,N-dimethylformamide at a ratio of 2-3g:10-15mL. The post-treatment includes: after the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80-100°C, and the reduced pressure distillation is performed until no liquid is produced to obtain a lightweight polyurethane.
[0041] Furthermore, the preparation method of the lightweight cable comprises the following steps:
[0042] S1. After the composite aerogel is coated on the surface of the conductor layer, a polyvinylidene fluoride wrapping tape is used to wrap the outside of the composite aerogel to obtain a lightweight shielding layer and a wrapping layer.
[0043] S2. Add the composite cable material into a twin-screw extruder, melt and extrude it around the surface of the sheath, and cool it naturally to obtain a lightweight cable.
[0044] Furthermore, the temperatures of the eight temperature zones of the twin-screw extruder from the feed port toward the discharge port are 200°C, 215°C, 215°C, 220°C, 220°C, 230°C, 230°C, and 240°C, respectively, and the main engine speed of the twin-screw extruder is 80-120rpm, and the pressure is 100-150 bar.
[0045] The present invention also proposes the application of lightweight and high-strength power cables based on composite materials, and applies the lightweight and high-strength power cables based on composite materials to aerospace, high-altitude cable construction, ship power supply and marine engineering.
[0046] The present invention has the following beneficial effects:
[0047] 1. The present invention uses nano calcium carbonate powder as a template to prepare carbon-coated nanospheres, removes calcium carbonate in an acidic potassium permanganate solution, oxidizes the carbon layer to obtain carbon shell hollow spheres, modifies the surface of the carbon spheres with a highly hydrolyzable silane coupling agent to obtain modified carbon spheres, and uses the modified carbon spheres as a filling material to hydrolyze tetrabutyl titanate to obtain a gel precursor, which is subjected to copper nitrate loading reduction to obtain a composite aerogel. The porous structure of the composite aerogel and the hollow carbon spheres cooperate to significantly reduce the density of the material, thereby significantly improving the lightweight performance of the material. In the process of preparing lightweight polyurethane, the modified carbon spheres are used as a filling material and a chain extender to hybridize the polyurethane segments and reduce the density of the polyurethane material. The complex spatial structure of the polyurethane segments and the spherical buffer structure of the modified carbon spheres significantly enhance the cantilever beam impact strength of the lightweight cable, thereby significantly improving the strength of the cable material.
[0048] 2. The copper particles in the composite aerogel structure prepared by the present invention help to evenly disperse heat and prevent local overheating due to their good thermal conductivity, thereby indirectly enhancing the thermal stability and high temperature resistance of the material. Titanium dioxide, as an inorganic compound with high thermal stability, can form a protective ceramic layer at high temperatures, effectively preventing the spread of flames and improving the overall flame retardant effect. The hollow carbon spheres in the composite aerogel structure and lightweight polyurethane utilize their porous structure and low density characteristics. The hollow carbon spheres form a carbonized layer and enhance the thermal isolation effect, preventing the spread of flames and helping to reduce heat conduction. They also provide additional thermal isolation protection with their low thermal conductivity and high specific surface area, optimizing the synergistic effect of other components, thereby enhancing the flame retardant ability of the overall material. Through the synergistic effect of these three, the cable can effectively delay the combustion process under high temperature and flame exposure conditions, prevent the spread of flames, and provide excellent flame retardant properties.
[0049] 3. The composite aerogel prepared by the present invention is used as a filling material for a lightweight shielding layer. The copper particles loaded in the structure absorb and reflect electromagnetic waves through their excellent conductivity. The titanium dioxide structure utilizes its semiconductor properties and strong photoelectric effect to enhance the absorption and reflection of high-frequency electromagnetic waves, and provides a better dispersion environment for the copper particles, thereby improving the overall shielding capability. The hollow carbon balls in the composite aerogel structure and lightweight polyurethane increase the reflection and scattering effects of the material and reduce the density by virtue of their porous structure, lightweight properties and conductivity, thereby making the material more balanced and efficient in resisting electromagnetic interference. In addition, the aerogel matrix, as a carrier, optimizes the coordination between copper particles, titanium dioxide and hollow carbon balls through its extremely low density and high specific surface area, so that electromagnetic waves are more reflected, scattered and absorbed inside the material. Through the synergistic effect of the three, the material's anti-electromagnetic interference performance is significantly improved. BRIEF DESCRIPTION OF THE DRAWINGS
[0050] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0051] Figure 1 This is a schematic diagram of the results of the lightweight cable prepared by the present invention.
[0052] In the figure: 100, conductor layer; 200, lightweight shielding layer; 300, wrapping layer; 400, composite sheath layer. DETAILED DESCRIPTION
[0053] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0054] The hydroxy silicone oil used in the present invention was purchased from Zhejiang Zhenghe Silicon Materials Co., Ltd., with a brand number of 207-35;
[0055] The nano calcium carbonate powder used in the present invention is purchased from Beijing Juguang Yingchuang Technology Co., Ltd., with the item number BM11268.
[0056] Example 1
[0057] This embodiment is used to provide a method for preparing modified carbon balls for lightweight and high-strength power cables based on composite materials, comprising the following steps:
[0058] Step ①: Preparation of carbon-coated nanospheres
[0059] Weigh: 100.0g of nano-calcium carbonate powder is dispersed in a hydrothermal reactor containing 2000.0mL of 0.5M glucose solution. The stirring rate of the reactor is 60rpm. After stirring at room temperature for 5min, the temperature of the hydrothermal reactor is increased to 140°C and the reaction is kept warm for 6h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is transferred to a drying oven at a temperature of 60°C for vacuum drying. After the filter cake reaches constant weight, the filter cake is transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 720°C at a heating rate of 5°C / min. After calcination for 5h, it is naturally cooled to obtain carbon-coated nanospheres.
[0060] Step ②: Preparation of carbon shell hollow spheres
[0061] Weigh: 200.0g carbon-coated nanospheres and 3000.0mL 49.0wt% sulfuric acid are added to the reactor, the stirring rate of the reactor is 60rpm, and after stirring at room temperature for 10min, 600.0g potassium permanganate is added to the reactor, the temperature of the reactor is raised to 40°C, and the reaction is kept warm for 1h. After the reaction is completed, after the temperature of the reactor is lowered to room temperature, a protective sodium hydroxide solution is added to the reactor, the reaction liquid is adjusted to be neutral, the reaction liquid is filtered to collect the filter cake, and the filter cake is washed 3 times with anhydrous ethanol and deionized water, and the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain a carbon shell hollow sphere.
[0062] Step ③: Preparation of modified carbon spheres
[0063] Weigh: 200.0 g of 3-isocyanate propyl trimethoxy silane and 1000.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0064] Weigh: 400.0g hollow carbon spheres and 3000.0mL N,N-dimethylformamide are added to the reactor, nitrogen protection is introduced, the stirring rate of the reactor is 60rpm, and after stirring at room temperature for 5min, 1000.0mL 3-isocyanatepropyltrimethoxysilane solution is added to the reactor, the temperature of the reactor is raised to 30°C, and the heat treatment is carried out for 30min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 3 times with anhydrous ethanol, and the filter cake is transferred to a drying oven at a temperature of 60°C and vacuum dried until the filter cake has a constant weight to obtain modified carbon spheres.
[0065] Example 2
[0066] This embodiment is used to provide a method for preparing modified carbon balls for lightweight and high-strength power cables based on composite materials, comprising the following steps:
[0067] Step ①: Preparation of carbon-coated nanospheres
[0068] Weigh: 200.0g of nano calcium carbonate powder is dispersed in a hydrothermal reactor filled with 24mL 0.8M glucose solution. The stirring rate of the reactor is 80rpm. After stirring at room temperature for 5min, the temperature of the hydrothermal reactor is increased to 140°C and the reaction is kept warm for 6h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is transferred to a drying oven at a temperature of 60°C for vacuum drying. After the filter cake has constant weight, the filter cake is transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 720°C at a heating rate of 5°C / min. After calcination for 5h, it is naturally cooled to obtain carbon-coated nanospheres.
[0069] Step ②: Preparation of carbon shell hollow spheres
[0070] Weigh: 300.0g carbon-coated nanospheres and 3600.0mL 49.0wt% sulfuric acid are added to the reactor, the stirring rate of the reactor is 80rpm, and after stirring at room temperature for 15min, 800.0g potassium permanganate is added to the reactor, the temperature of the reactor is raised to 50°C, and the reaction is kept warm for 2h. After the reaction is completed, after the temperature of the reactor is lowered to room temperature, a protective sodium hydroxide solution is added to the reactor, the reaction liquid is adjusted to be neutral, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 5 times with anhydrous ethanol and deionized water, and the filter cake is transferred to a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain a carbon shell hollow sphere.
[0071] Step ③: Preparation of modified carbon spheres
[0072] Weigh: 300.0 g of 3-isocyanate propyl trimethoxy silane and 1500.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0073] Weigh: 500.0g hollow carbon spheres and 4000.0mL N,N-dimethylformamide are added to the reactor, nitrogen is introduced for protection, the stirring rate of the reactor is 80rpm, and after stirring at room temperature for 8min, 1200.0mL 3-isocyanatepropyltrimethoxysilane solution is added to the reactor, the temperature of the reactor is raised to 50°C, and the heat treatment is carried out for 40min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 5 times with anhydrous ethanol, and the filter cake is transferred to a drying oven at a temperature of 80°C and vacuum dried until the filter cake has a constant weight to obtain modified carbon spheres.
[0074] Example 3
[0075] This embodiment is used to provide a method for preparing modified carbon balls for lightweight and high-strength power cables based on composite materials, comprising the following steps:
[0076] Step ①: Preparation of carbon-coated nanospheres
[0077] Weigh: 150.0g of nano calcium carbonate powder is dispersed in a hydrothermal reactor filled with 2100.0mL 0.6M glucose solution. The stirring rate of the reactor is 70rpm. After stirring at room temperature for 8min, the temperature of the hydrothermal reactor is increased to 150°C and the reaction is kept warm for 7h. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, and the filter cake is transferred to a drying oven at a temperature of 70°C for vacuum drying. After the filter cake has constant weight, the filter cake is transferred to a tubular furnace. After nitrogen protection is introduced, the tubular furnace is heated to 720°C at a heating rate of 5°C / min. After calcination for 5h, it is naturally cooled to obtain carbon-coated nanospheres.
[0078] Step ②: Preparation of carbon shell hollow spheres
[0079] Weigh: 250.0g carbon-coated nanospheres and 3200.0mL 49.0wt% sulfuric acid are added to the reactor. The stirring rate of the reactor is 70rpm. After stirring at room temperature for 12min, 700.0g potassium permanganate is added to the reactor. The temperature of the reactor is raised to 45°C and the reaction is kept warm for 2h. After the reaction is completed, after the temperature of the reactor is lowered to room temperature, a protective sodium hydroxide solution is added to the reactor to adjust the reaction liquid to be neutral. The reaction liquid is filtered to collect the filter cake, and the filter cake is washed 4 times with anhydrous ethanol and deionized water. The filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried until the filter cake has a constant weight to obtain a carbon shell hollow sphere.
[0080] Step ③: Preparation of modified carbon spheres
[0081] Weigh: 250.0 g of 3-isocyanate propyl trimethoxy silane and 1200.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0082] Weigh: 450.0g hollow carbon spheres and 3600.0mL N,N-dimethylformamide are added to the reactor, nitrogen protection is introduced, the stirring rate of the reactor is 70rpm, and after stirring at room temperature for 6min, 1100.0mL 3-isocyanatepropyltrimethoxysilane solution is added to the reactor, the temperature of the reactor is raised to 40°C, and the heat treatment is carried out for 35min. After the reaction is completed, the temperature of the reactor is lowered to room temperature, the reaction liquid is filtered to collect the filter cake, the filter cake is washed 4 times with anhydrous ethanol, and the filter cake is transferred to a drying oven at a temperature of 70°C and vacuum dried until the filter cake has a constant weight to obtain modified carbon spheres.
[0083] Example 4
[0084] This embodiment is used to provide a method for preparing a composite aerogel for a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0085] Step (1) Preparation of composite liquid
[0086] Weigh: 100.0 g of copper nitrate and 800.0 mL of ethylene glycol to obtain a copper source solution;
[0087] Weigh: 400.0 g of the modified carbon spheres prepared in Example 1, 700.0 g of tetrabutyl titanate and 6000.0 mL of deionized water are added into a reactor at a stirring rate of 60 rpm. After stirring at room temperature for 10 min, 1000.0 mL of copper source solution is added dropwise into the reactor and stirring is continued for 5 min to obtain a composite solution.
[0088] Step (2): preparing a gel precursor
[0089] Weigh: 3000.0mL of the composite liquid is transferred to a hydrothermal reactor, the temperature of the hydrothermal reactor is raised to 160°C, and the reaction is kept warm for 20 hours. After the reaction is completed, after the temperature of the hydrothermal reactor is lowered to room temperature, the material is transferred to a stainless steel mold, and the stainless steel mold is transferred to a copper column immersed in liquid nitrogen. After standing for 20 minutes, the mold is transferred to a vacuum dryer, the temperature is set to 30°C, the vacuum degree is 3mBar, and vacuum drying is performed for 1 hour to obtain a gel precursor.
[0090] Step (3): preparing composite aerogel
[0091] Weigh: 1000.0 g of the gel precursor was transferred to a tubular furnace. After nitrogen protection was introduced into the tubular furnace, the temperature was increased to 400°C at a heating rate of 3°C / min. The nitrogen was then disconnected, and a mixed gas of hydrogen and nitrogen with a volume ratio of 4 mL:95 mL was introduced into the tubular furnace. The mixture was kept warm for 30 min and naturally cooled to room temperature to obtain a composite aerogel.
[0092] Example 5
[0093] This embodiment is used to provide a method for preparing a composite aerogel for a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0094] Step (1) Preparation of composite liquid
[0095] Weigh: 200.0 g of copper nitrate and 1000.0 mL of ethylene glycol to obtain a copper source solution;
[0096] Weigh: 600.0 g of modified carbon spheres prepared in Example 2, 800.0 g of tetrabutyl titanate and 8000.0 mL of deionized water are added into a reactor with a stirring rate of 80 rpm. After stirring at room temperature for 15 min, 2000.0 mL of copper source solution is added dropwise into the reactor and stirring is continued for 8 min to obtain a composite solution.
[0097] Step (2): preparing a gel precursor
[0098] Weigh: 3000.0mL of the composite liquid is transferred to a hydrothermal reactor, the temperature of the hydrothermal reactor is raised to 200°C, and the reaction is kept warm for 28 hours. After the reaction is completed, after the temperature of the hydrothermal reactor is lowered to room temperature, the material is transferred to a stainless steel mold, and the stainless steel mold is transferred to a copper column immersed in liquid nitrogen. After standing for 30 minutes, the mold is transferred to a vacuum dryer, the temperature is set to 50°C, the vacuum degree is 5mBar, and vacuum drying is performed for 2 hours to obtain a gel precursor.
[0099] Step (3): preparing composite aerogel
[0100] Weigh: 1000.0 g of the gel precursor was transferred to a tubular furnace. After nitrogen protection was introduced into the tubular furnace, the temperature was increased to 500° C. at a heating rate of 5° C. / min. The nitrogen was disconnected, and a mixed gas of hydrogen and nitrogen with a volume ratio of 5 mL:95 mL was introduced into the tubular furnace. The mixture was kept warm for 40 min and naturally cooled to room temperature to obtain a composite aerogel.
[0101] Example 6
[0102] This embodiment is used to provide a method for preparing a composite aerogel for a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0103] Step (1) Preparation of composite liquid
[0104] Weigh: 150.0 g of copper nitrate and 900.0 mL of ethylene glycol to obtain a copper source solution;
[0105] Weigh: 500.0 g of the modified carbon spheres prepared in Example 3, 750.0 g of tetrabutyl titanate and 7200.0 mL of deionized water were added into a reactor with a stirring rate of 70 rpm. After stirring at room temperature for 12 min, 1600.0 mL of copper source solution was added dropwise into the reactor and stirring was continued for 6 min to obtain a composite solution.
[0106] Step (2): preparing a gel precursor
[0107] Weigh: 3000.0mL of the composite liquid is transferred to a hydrothermal reactor, the temperature of the hydrothermal reactor is raised to 180.0°C, and the reaction is kept warm for 24 hours. After the reaction is completed, after the temperature of the hydrothermal reactor is lowered to room temperature, the material is transferred to a stainless steel mold, and the stainless steel mold is transferred to a copper column immersed in liquid nitrogen. After standing for 25 minutes, the mold is transferred to a vacuum dryer, the temperature is set to 40°C, the vacuum degree is 4mBar, and vacuum drying is performed for 1 hour to obtain a gel precursor.
[0108] Step (3): preparing composite aerogel
[0109] Weigh 1000.0 g of the gel precursor and transfer it to a tubular furnace. After nitrogen protection is introduced into the tubular furnace, the temperature is raised to 450.0°C at a heating rate of 4°C / min. Then, the nitrogen is disconnected and a mixed gas of hydrogen and nitrogen with a volume ratio of 5 mL:95 mL is introduced into the tubular furnace. The mixture is kept warm for 35 min and naturally cooled to room temperature to obtain a composite aerogel.
[0110] Example 7
[0111] This embodiment is used to provide a method for preparing a lightweight polyurethane for a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0112] Step Ⅰ: Preparation of modified polyurethane
[0113] Weigh: 300.0 g of m-phenylenedimethyl isocyanate and 1000.0 mL of N,N-dimethylformamide to obtain a m-phenylenedimethyl isocyanate solution;
[0114] Weigh: 800.0g hydroxy silicone oil, 100.0g hydroquinone dihydroxyethyl ether, 4000.0mL N,N-dimethylformamide and 20.0g dibutyltin dilaurate are added to a reactor. After nitrogen protection, 1000.0mL of meta-phenylenedimethyl isocyanate solution is added to the reactor. The temperature of the reactor is increased to 50°C and the reaction is kept warm for 4h. After the reaction is completed, purified water is added to the reactor. The temperature of the reactor is increased to 120°C and distilled under reduced pressure until no liquid is produced to obtain a modified polyurethane.
[0115] Step II: Preparation of lightweight polyurethane
[0116] Weigh: 300.0 g of 3-isocyanate propyl trimethoxy silane and 1000.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0117] Weigh: 800.0g of modified polyurethane and 4000.0mL of N,N-dimethylformamide are added to a reactor and stirred at a stirring rate of 60rpm. After the temperature of the reactor is raised to 40°C, 1000.0mL of 3-isocyanatepropyltrimethoxysilane solution is added to the reactor. After stirring for 30 minutes, deionized water and sodium hydroxide powder are added to the reactor. After stirring for 5 minutes, 200.0g of modified carbon balls prepared in Example 1 are added to the reactor. The reaction is kept warm for 20 minutes. After the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 80°C, and distilled under reduced pressure until no liquid is produced to obtain a lightweight polyurethane.
[0118] Example 8
[0119] This embodiment is used to provide a method for preparing a lightweight polyurethane for a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0120] Step Ⅰ: Preparation of modified polyurethane
[0121] Weigh: 400.0 g of m-phenylenedimethyl isocyanate and 1500.0 mL of N,N-dimethylformamide to obtain a m-phenylenedimethyl isocyanate solution;
[0122] Weigh: 1000.0g hydroxy silicone oil, 200.0g hydroquinone dihydroxyethyl ether, 6000.0mL N,N-dimethylformamide and 50.0g dibutyltin dilaurate are added to a reactor. After nitrogen protection, 1200.0mL of meta-phenylenedimethyl isocyanate solution is added to the reactor. The temperature of the reactor is increased to 60°C and the reaction is kept warm for 2h. After the reaction is completed, purified water is added to the reactor. The temperature of the reactor is increased to 140°C and distilled under reduced pressure until no liquid is produced to obtain a modified polyurethane.
[0123] Step II: Preparation of lightweight polyurethane
[0124] Weigh: 400.0 g of 3-isocyanate propyl trimethoxy silane and 1500.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0125] Weigh: 1000.0g of modified polyurethane and 5000.0mL of N,N-dimethylformamide are added to a reactor and stirred at a stirring rate of 60-80rpm. After the temperature of the reactor is raised to 60°C, 1500.0mL of 3-isocyanatepropyltrimethoxysilane solution is added to the reactor. After stirring and insulating for 40 minutes, deionized water and sodium hydroxide powder are added to the reactor. After stirring and insulating for 8 minutes, 300.0g of modified carbon balls prepared in Example 2 are added to the reactor. The reaction is insulated for 30 minutes. After the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 100°C, and distilled under reduced pressure until no liquid is produced to obtain a lightweight polyurethane.
[0126] Example 9
[0127] This embodiment is used to provide a method for preparing a lightweight polyurethane for a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0128] Step Ⅰ: Preparation of modified polyurethane
[0129] Weigh: 350.0 g of m-phenylenedimethyl isocyanate and 1200.0 mL of N,N-dimethylformamide and mix to obtain a m-phenylenedimethyl isocyanate solution;
[0130] Weigh: 900.0g hydroxy silicone oil, 160.0g hydroquinone dihydroxyethyl ether, 5000.0mL N,N-dimethylformamide and 350.0g dibutyltin dilaurate are added to a reactor. After nitrogen protection, 1100.0mL of meta-xylylene diisocyanate solution is added to the reactor. The temperature of the reactor is increased to 54°C and the reaction is kept warm for 2h. After the reaction is completed, purified water is added to the reactor. The temperature of the reactor is increased to 130°C and distilled under reduced pressure until no liquid is produced to obtain a modified polyurethane.
[0131] Step II: Preparation of lightweight polyurethane
[0132] Weigh: 350.0 g of 3-isocyanate propyl trimethoxy silane and 1200.0 mL of N,N-dimethylformamide and mix to obtain a 3-isocyanate propyl trimethoxy silane solution;
[0133] Weigh: 900.0g of modified polyurethane and 4500.0mL of N,N-dimethylformamide are added to a reactor and stirred at a stirring rate of 70rpm. After the temperature of the reactor is raised to 50°C, 1200.0mL of 3-isocyanatepropyltrimethoxysilane solution is added to the reactor. After stirring for 35 minutes, deionized water and sodium hydroxide powder are added to the reactor. After stirring for 6 minutes, 250.0g of modified carbon balls prepared in Example 3 are added to the reactor. The reaction is kept warm for 24 minutes. After the reaction is completed, the reactor is cooled to room temperature, the reaction solution is added to a rotary evaporator with a water bath temperature of 90°C, and distilled under reduced pressure until no liquid is produced to obtain a lightweight polyurethane.
[0134] Example 10
[0135] This embodiment is used to provide a method for preparing a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0136] Step 1: Prepare lightweight shielding layer and wrapping layer
[0137] After the composite aerogel prepared in Example 4 is coated on the surface of the conductor layer 100 , a polyvinylidene fluoride wrapping tape is then used to wrap the outside of the composite aerogel to obtain a lightweight shielding layer 200 and a wrapping layer 300 .
[0138] Step 2: Prepare lightweight cables
[0139] Weigh: 7000.0g of the lightweight polyurethane prepared in Example 7, 1000.0g of hexabromocyclododecane, 500.0g of dioctyl phthalate, 20.0g of 2-hydroxy-4-octyloxybenzophenone and 300.0g of calcium stearate and add them to a twin-screw extruder. The temperatures of the eight temperature sections of the twin-screw extruder from the feed port toward the discharge port are 200°C, 215°C, 215°C, 220°C, 220°C, 230°C, 230°C, and 240°C, respectively. The main engine speed of the twin-screw extruder is 80rpm, the pressure is 100 bar, the molten extrusion is wrapped around 300 surfaces, and the lightweight cable is naturally cooled.
[0140] Embodiment 11
[0141] This embodiment is used to provide a method for preparing a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0142] Step 1: Prepare lightweight shielding layer and wrapping layer
[0143] After the composite aerogel prepared in Example 5 is coated on the surface of the conductor layer 100 , a polyvinylidene fluoride wrapping tape is used to wrap the outside of the composite aerogel to obtain a lightweight shielding layer 200 and a wrapping layer 300 .
[0144] Step 2: Prepare lightweight cables
[0145] Weigh: 8500.0g of the lightweight polyurethane prepared in Example 8, 1500.0g of hexabromocyclododecane, 800.0g of dioctyl phthalate, 50.0g of 2-hydroxy-4-octyloxybenzophenone and 500.0g of calcium stearate are added to a twin-screw extruder, and the temperatures of the eight temperature sections of the twin-screw extruder from the feed port toward the discharge port are 200°C, 215°C, 215°C, 220°C, 220°C, 230°C, 230°C, 240°C, the main engine speed of the twin-screw extruder is 120rpm, the pressure is 150bar, the melt extrusion is wrapped around the 300 surface of the cladding layer, and the lightweight cable is obtained by natural cooling.
[0146] Example 12
[0147] This embodiment is used to provide a method for preparing a lightweight and high-strength power cable based on a composite material, comprising the following steps:
[0148] Step 1: Prepare lightweight shielding layer and wrapping layer
[0149] After the composite aerogel prepared in Example 6 is coated on the surface of the conductor layer 100 , a polyvinylidene fluoride wrapping tape is used to wrap the outside of the composite aerogel to obtain a lightweight shielding layer 200 and a wrapping layer 300 .
[0150] Step 2: Prepare lightweight cables
[0151] Weigh: 8100.0g of the lightweight polyurethane prepared in Example 9, 1200.0g of hexabromocyclododecane, 720.0g of dioctyl phthalate, 35.0g of 2-hydroxy-4-octyloxybenzophenone and 400.0g of calcium stearate and add them into a twin-screw extruder. The temperatures of the eight temperature sections of the twin-screw extruder from the feed port toward the discharge port are 200°C, 215°C, 215°C, 220°C, 220°C, 230°C, 230°C, and 240°C, respectively. The main engine speed of the twin-screw extruder is 100rpm, the pressure is 120bar, the surface of the cladding layer is 300°C, and it is naturally cooled to obtain a lightweight cable.
[0152] Comparative Example 1
[0153] The difference between this comparative example and Example 12 is that, in the preparation process of the lightweight polyurethane used in step 1, step II is eliminated and an equal amount of modified polyurethane is used to replace the lightweight polyurethane.
[0154] Comparative Example 2
[0155] The difference between this comparative example and Example 12 is that in the preparation process of the composite aerogel used in step 2, the use of modified carbon balls in step ⑴ is eliminated.
[0156] Comparative Example 3
[0157] The difference between this comparative example and Example 12 is that in the preparation process of the composite aerogel used in step 2, the use of the copper source solution in step (1) is eliminated.
[0158] Performance Testing:
[0159] The tensile strength of the lightweight cables prepared in Examples 10-12 and Comparative Examples 1-3 was tested with reference to Standard XF 306.1-2007 "Classification and Requirements for Flame Retardant and Fire Resistant Cables Plastic Insulated Flame Retardant and Fire Resistant Cables Part 1: Flame Retardant Cables";
[0160] The anti-electromagnetic interference performance of the lightweight cables prepared in Examples 10-12 and Comparative Examples 1-3 was tested with reference to the standard GB / T 32511-2016 "General Technical Requirements for Electromagnetic Shielding Plastics";
[0161] The flame retardant grades of the lightweight cables prepared in Examples 10-12 and Comparative Examples 1-3 were tested with reference to Standard XF 306.1-2007 "Classification and requirements for flame retardant and fire resistant cables, plastic insulated flame retardant and fire resistant cables, Part 1: Flame retardant cables";
[0162] The density of the composite sheath layer prepared in Examples 10-12 and Comparative Examples 1-3 was tested with reference to the standard GB / T 1033.2-2010 "Determination of density of plastics, non-foamed plastics - Part 2: Density gradient column method";
[0163] The density of the composite aerogels used in Examples 10-12 and Comparative Examples 1-3 was measured with reference to the standard GB / T 1033.2-2010 "Determination of density of non-foamed plastics Part 2: Density gradient column method", and the specific data are shown in Table 1.
[0164] Table 1-Performance test data of each sample
[0165] Project Category Example 10 Embodiment 11 Example 12 Comparative Example 1 Comparative Example 2 Comparative Example 3 Tensile strength / MPa 25.3 26.1 27.2 13.2 21.3 20.2 Anti-electromagnetic interference performance / level SE-1 SE-1 SE-1 SE-2 SE-2 SE-2 Flame retardant grade / level ⅠA ⅠA ⅠA ⅠB ⅠC ⅠB <![CDATA[Composite protective sleeve density / g·cm -3 > 0.2785 0.2732 0.2691 0.7215 0.2815 0.2824 <![CDATA[Composite aerogel density / g·cm -3 > 0.25 0.24 0.24 0.26 0.48 0.22
[0166] Data Analysis:
[0167] By comparing and analyzing the data in Table 1, it can be found that the tensile strength of the lightweight cable prepared by the present invention is 27.2MPa, the anti-electromagnetic interference performance is SE-1 level and the flame retardant grade is IA, and the density of the composite sheath layer is 0.2691g·cm -3 The density of the composite aerogel is 0.24 g·cm -3 , all performance test data are better than the comparative example;
[0168] Description: The present invention uses nano calcium carbonate powder as a template to prepare carbon-coated nanospheres, removes calcium carbonate in an acidic potassium permanganate solution, and oxidizes the carbon layer to obtain carbon shell hollow spheres, modifies the surface of the carbon spheres with a highly hydrolyzable silane coupling agent to obtain modified carbon spheres, and uses the modified carbon spheres as a filling material to hydrolyze tetrabutyl titanate to obtain a gel precursor, which is subjected to copper nitrate loading reduction to obtain a composite aerogel. The porous structure of the composite aerogel and the hollow carbon spheres cooperate to significantly reduce the density of the material, thereby significantly improving the lightweight performance of the material. In the process of preparing lightweight polyurethane, the modified carbon spheres are used as a filling material and a chain extender to hybridize the polyurethane segments and reduce the density of the polyurethane material. The complex spatial structure of the polyurethane segments and the spherical buffer structure of the modified carbon spheres significantly enhance the cantilever beam impact strength of the lightweight cable, thereby significantly improving the strength of the cable material.
[0169] It is explained that the copper particles in the composite aerogel structure prepared by the present invention help to evenly disperse heat and prevent local overheating due to their good thermal conductivity, thereby indirectly enhancing the thermal stability and high temperature resistance of the material. Titanium dioxide, as an inorganic compound with high thermal stability, can form a protective ceramic layer at high temperature, effectively preventing the spread of flames and improving the overall flame retardant effect. The hollow carbon spheres in the composite aerogel structure and lightweight polyurethane utilize their porous structure and low density characteristics. The hollow carbon spheres form a carbonized layer and enhance the thermal isolation effect, preventing the spread of flames and helping to reduce heat conduction. They also provide additional thermal isolation protection with their low thermal conductivity and high specific surface area, optimizing the synergistic effect of other components, thereby enhancing the flame retardant ability of the overall material. Through the synergistic effect of these three, the cable can effectively delay the combustion process under high temperature and flame exposure conditions, prevent the spread of flames, and provide excellent flame retardant properties.
[0170] It is explained that the composite aerogel prepared by the present invention is used as a filling material for a lightweight shielding layer. The copper particles loaded in the structure absorb and reflect electromagnetic waves through their excellent electrical conductivity. The titanium dioxide structure utilizes its semiconductor properties and strong photoelectric effect to enhance the absorption and reflection effects of high-frequency electromagnetic waves, and provides a better dispersion environment for the copper particles, thereby improving the overall shielding ability. The hollow carbon balls in the composite aerogel structure and lightweight polyurethane increase the reflection and scattering effects of the material and reduce the density by virtue of their porous structure, lightweight properties and electrical conductivity, thereby making the material more balanced and efficient in resisting electromagnetic interference. In addition, the aerogel matrix, as a carrier, optimizes the coordination between copper particles, titanium dioxide and hollow carbon balls through its extremely low density and high specific surface area, thereby enabling electromagnetic waves to be more reflected, scattered and absorbed inside the material. Through the synergistic effect of the three, the anti-electromagnetic interference performance of the material is significantly improved.
[0171] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A lightweight and high-strength power cable based on composite materials, characterized in that: It comprises a conductor layer (100), a lightweight shielding layer (200), a wrapping layer (300) and a composite sheath layer (400) which are arranged in sequence from the inside to the outside; The conductor layer (100) is composed of a plurality of copper wires twisted together and coated with polyvinylidene fluoride; the wrapping layer (300) is obtained by wrapping a polyvinylidene fluoride wrapping tape around the outside of the composite aerogel; and the composite sheath layer (400) is composed of a composite cable material; The lightweight shielding layer (200) is obtained by coating the conductor layer (100) with a composite aerogel and fixing it with a wrapping tape; the composite sheath layer (400) is obtained by melt-extruding a composite cable material onto the surface of the wrapping layer (300) and shaping it, wherein the composite cable material is a mixture of lightweight polyurethane, flame retardant, plasticizer, ultraviolet absorber and lubricant in a mass ratio of 70-85g:10-15g:5-8g:0.2-0.5g:3-5g.
2. The lightweight and high-strength power cable based on composite materials according to claim 1, characterized in that: The preparation method of the composite aerogel comprises the following steps: A1. Add modified carbon spheres, tetrabutyl titanate and deionized water into a reactor, stir at room temperature for 10-15 minutes, then dropwise add copper source solution into the reactor, and continue stirring for 5-8 minutes to obtain a composite solution; A2, transferring the composite liquid to a hydrothermal reactor, raising the temperature of the hydrothermal reactor to 160-200°C, keeping the temperature for 20-28h, and post-treating to obtain a gel precursor; A3. Transfer the gel precursor to a tubular furnace and calcine and reduce it to obtain a composite aerogel.
3. The lightweight and high-strength power cable based on composite materials according to claim 2, characterized in that: In step A1, the amount ratio of modified carbon spheres, tetrabutyl titanate, deionized water and copper source solution is 4-6g:7-8g:60-80mL:10-20mL, and the copper source solution is obtained by mixing copper nitrate and ethylene glycol in an amount ratio of 1-2g:8-10mL; in step A3, the calcination reduction operation is as follows: after nitrogen protection is introduced into the tubular furnace, the temperature is increased to 400-500°C at a heating rate of 3-5°C / min, the nitrogen is disconnected, and a mixed gas of hydrogen and nitrogen in a volume ratio of 4-5mL:95mL is introduced into the tubular furnace, and the mixture is kept warm for 30-40min and naturally cooled to room temperature to obtain a composite aerogel.
4. The lightweight and high-strength power cable based on composite materials according to claim 2, characterized in that: The preparation method of the modified carbon spheres comprises the following steps: B1. Disperse nano-calcium carbonate powder in a hydrothermal reactor filled with a carbon source solution, stir for 5-8 minutes at room temperature, raise the temperature of the hydrothermal reactor to 140-160°C, keep the reaction for 6-8 hours, and post-treat to obtain carbon-coated nanospheres; B2, adding carbon-coated nanospheres and 49.0wt% sulfuric acid into a reactor, stirring at room temperature for 10-15min, adding potassium permanganate into the reactor, raising the temperature of the reactor to 40-50°C, keeping the temperature for 1-2h, and post-treating to obtain carbon shell hollow spheres; B3. Add hollow carbon spheres and N,N-dimethylformamide into a reactor, introduce nitrogen protection, stir at room temperature for 5-8 minutes, add 3-isocyanatepropyltrimethoxysilane solution into the reactor, increase the temperature of the reactor to 30-50°C, keep warm for 30-40 minutes, and post-treat to obtain modified carbon spheres.
5. The lightweight and high-strength power cable based on composite materials according to claim 4, characterized in that: In step B1, the dosage ratio of nano calcium carbonate powder and carbon source solution is 1-2g:20-24mL, and the carbon source solution is a glucose solution with a concentration of 0.5-0.8M; in step B2, the dosage ratio of carbon-coated nanospheres, 49.0wt% sulfuric acid and potassium permanganate is 2-3g:30-36mL:6-8g.
6. The lightweight and high-strength power cable based on composite materials according to claim 4, characterized in that: In step B3, the amount ratio of the hollow carbon sphere, N,N-dimethylformamide and 3-isocyanate propyltrimethoxysilane solution is 4-5g:30-40mL:10-12mL, and the 3-isocyanate propyltrimethoxysilane solution is obtained by mixing 3-isocyanate propyltrimethoxysilane and N,N-dimethylformamide in an amount ratio of 2-3g:10-15mL.
7. The lightweight and high-strength power cable based on composite materials according to claim 1, characterized in that: The preparation method of the lightweight polyurethane comprises the following steps: C1. Add hydroxy silicone oil, hydroquinone dihydroxyethyl ether, N,N-dimethylformamide and dibutyltin dilaurate into a reactor, introduce nitrogen protection, add meta-xylyl diisocyanate solution into the reactor, increase the temperature of the reactor to 50-60°C, keep the reaction temperature for 1-2h, and post-treat to obtain modified polyurethane; C2. Add modified polyurethane and N,N-dimethylformamide into a reactor and stir. After the temperature of the reactor rises to 40-60°C, add 3-isocyanatepropyltrimethoxysilane solution into the reactor. After stirring for 30-40 minutes, add deionized water and sodium hydroxide powder into the reactor. After stirring for 5-8 minutes, add modified carbon balls into the reactor. Keep warm for 20-30 minutes, and obtain lightweight polyurethane by post-treatment.
8. The lightweight and high-strength power cable based on composite materials according to claim 7, characterized in that: In step C1, the amount ratio of hydroxy silicone oil, dihydroxyethyl hydroquinone, N,N-dimethylformamide, dibutyltin dilaurate and meta-phenylenedimethyl isocyanate solution is 8-10g:1-2g:40-60mL:0.2-0.5g:10-12mL; in step C2, the amount ratio of modified polyurethane, N,N-dimethylformamide, 3-isocyanatepropyltrimethoxysilane solution and modified carbon sphere is 8-10g:40-50mL:10-15mL:2-3g.
9. Application of lightweight and high-strength power cables based on composite materials, characterized in that: The lightweight and high-strength power cables based on composite materials described in claims 1 to 8 are applied to aerospace, high-altitude cable construction, ship power supply and marine engineering.
Citation Information
Patent Citations
Communication cable for ships
CN104795171A
Carbon hollow sphere aerogel, and preparation method and application thereof
CN108689397A
Wear-resistant and tear-resistant silicone rubber wire and cable and preparation method thereof
CN114974684A
High frequency response cable tied in a bundle for intelligence mechanical arm
CN208157105U
All-aerogel wire
CN211350146U
Cited By
Flame-retardant aging-resistant cable for solar power generation and preparation method thereof
CN120137409A